Female Subjectivities in African Literature. - Smith, Charles (Handel Books, 2015)
In literature the ambiguous portraiture of female characters by some male writers and the phallic nature of men's writings have proved a matter of concern to female writers in Africa. For decades within African writing the issue of silencing was interrogated particularly as it addressed the muting and marginalisation of black women by male writers through the script of patriarchy which men follow. In this series we continue the literary and dramatic tradition of feminist concern for women's issues and we review novels, plays and poetry which demonstrate a commitment to exploring the challenges facing modern women in changing times and excerpting the issues of gender, feminism, identity, race, history, national and international politics specifically as they affect women. Female Subjectivities collectively answers the need to question and adumbrate the possibilities of literary revisions, showing what it would mean to revise even the Feminist psychoanalyst in a discourse on the subjectivity of women of colour.